Environmental tobacco smoke exposure and diabetes in adult never-smokers - Eze, Ikenna C; Schaffner, Emmanuel; Zemp, Elisabeth; von Eckardstein, Arnold; Turk, Alexander; Bettschart, Robert; Schindler, Christian; Probst-Hensch, Nicole (Environmental health, 2014)
Background Active smoking has been linked to type 2 diabetes mellitus (T2DM) but only few recent studies have shown environmental tobacco smoke (ETS) to be associated with DM in never-smokers. We assessed the association between long term ETS exposure and DM, and explored effect modifications of this association in our sample. Methods We analysed 6392 participants of the Swiss study on air pollution and lung and heart diseases in adults (SAPALDIA). We used mixed logistic regression models to assess the cross-sectional association between ETS and DM. Selected variables were tested for effect modification and several sensitivity analyses were performed, mostly treating participants’ study area as a random effect. Results The prevalence of DM and ETS in the sample was 5.5% and 47% respectively. There were 2779 never-smokers with 4% diabetes prevalence. Exposure to ETS increased risk of DM in never-smokers by 50% [95% confidence interval (CI): 1.00, 2.26], and we observed a positive dose–response relationship between ETS exposure level and DM in never-smokers. Associations were strengthened (more than three-folds) by older age and chronic obstructive pulmonary disease, and were stronger in post-menopausal, obese, hypertriglyceridaemic and physically inactive participants. Estimates of association were robust across all sensitivity analyses (including inverse probability weighting for participation bias and fixed-effect analysis for study area). ETS had no substantial associations in current and ex-smokers in our study. Conclusions We found a positive association between ETS exposure and DM in never smokers. Additional longitudinal studies involving biomarkers are needed to further explore underlying mechanisms and susceptibilities.